Investigations on effect of graphitic carbon nitride loading on the properties and electrochemical performance of g-C3N4/TiO2 nanocomposites for energy storage device applications. (January 2021) - Ranjithkumar, R.; Lakshmanan, P.; Devendran, P.; Nallamuthu, N.; Sudhahar, S.; Kumar, M. Krishna
Abstract: The g-C3 N4 /TiO2 nanocomposites samples have been prepared by thermal spreading method. The effects of carbon nitride loading on the physical and electro-chemical properties of g-C 3 N4 /TiO2 have been studied. The surface of Titania (TiO2 ) could be progressively covered with amorphous carbon nitride effectively for different loads. The consequent changes in the structure, morphology and optical properties were probed by spectroscopic techniques. The resulting changes in the electrochemical behaviour also analysed. The combined results of X-ray Diffraction (XRD), Fourier Transform Infra-Red spectroscopy (FTIR), Ultra Violet-Visible (UV–Vis), Raman studies showed that, the structure of g-C3 N4 /TiO2 changes from highly dispersed to bulk-like form with increasing loading. EDAX results were analysed to understand the proportions and loading variations of g-C3 N4 /TiO2 and optimum loading for electrochemical enhancements. The consequent changes in the electrochemical behaviour were revealed. Among different loadings, the 33% g-C3 N4 /TiO2 composite exhibited high specific capacitance. It exhibited good electrochemical performance in the cycling tests of charge-discharge analysis too. The prepared g-C3 N4 /TiO2 nanocomposite was examined in terms of supercapacitor behaviour from the charge-discharge curve and found the higher the specific capacitance of about 864.5 F/g. The cyclic performance test was examined to the g-C3 N4 /TiO2 nanocomposite for 2000 cycles and found excellent retention. Highlights: Progressively covered TiO2 by the g-C3 N4 via simple thermal spreading method. Studied the effects of carbon nitride loading on the physical and electro-chemical properties of g-C3 N4 /TiO2 . The optimum loading of carbon nitride over titania was found to be 33 wt%. Found the higher specific capacitance using g-C3 N4 /TiO2 of about 864.5 F/g at 1 mV s −1 .